Da Arquitectura. Do propósito vocacional - Condições|Estações - Maria Alice Fernandes Marques (2017)
This dissertation seeks to give news of the commitment toarchitecture, exposing the personal interest in design andpractice by clarifying the principles to follow in your exercise.The process of formation of each architect is unique, resultingin the display of an idea something diffuse about architecturethat reveals an interest in thinking and doing. The work revealsthe need to make the route operating through the organisationof personal experiences, crossing, clarifying and deepeningthem, building logics that contribute to establish ideas.A ref lection should incorporate both the theory and thepractice, where they both support each other. The work isdivided into four modules that match the circumstancesassociated with the learning process, being more a motivatorof themes that are considered fundamental in the practiceof architecture. The exposure of personal experiences isinsufficient and is therefore established a relationship withthe theoretical resources, obtaining an informative mattertransferable.Each experience gives rise to unique problems that allowyou to ref lect on fundamental contents in the practice ofarchitecture, that when identified and studied contribute tothe process of discovery and evolution of vocational purpose.The circumstances studied are then combined and enhanced,making evolve the fundamental matter of the dissertation,becoming more than references because configure projectalarms.